Analisis Kemampuan Peserta Didik Sekolah Dasar dalam Menemukan Unsur-unsur Paragraf pada Teks Bacaan - Husnun Najiyah; Sa'dun Akbar; M. Imron Rosyadi (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2019)
The purpose of this study was to describe students' ability to find paragraph elements in the reading text. The research method used was a mix of research methods with explanatory sequential research designs. Data collection techniques consisted of tests, interviews, and documentation. The research object was 34 students. Students' ability to find the main sentence in reading texts; 1, 2, and 3 shows sufficient criteria (60.77%) of a maximum score of 100%. The ability of students to find the main ideas in reading texts 1, 2, and 3 showed very fewer criteria (0%) than a maximum score of 100%. Students' ability to find explanatory sentences in the reading texts 1, 2 and 3 with sufficient criteria (55, 01%) from a maximum score of 100%. In general, the students’ mistakes were because they lack attention to teacher explanations and practice questions in finding elements of the paragraph.